Intramedullary spinal cord paracoccidioidomycosis: report of two cases Granuloma paracoccidioidomicótico intramedular: relato de dois casos - Benedicto Oscar Colli; João Alberto Assirati Jr; Hélio Rubens Machado; José Fernando de Castro Figueiredo; Leila Chimelli; Carmine Porcelli Salvarani; Fábio dos Santos (Arquivos de Neuro-Psiquiatria)
Two cases of intramedullary paracoccidioidomycosis are reported. Paracoccidioidomycosis is a systemic disease that involves the buccopharyngeal mucosa, lungs, lymph nodes and viscera and infrequently the central nervous system. Localization in the spinal cord is rare. Case 1: a 55-year old male admitted with crural pararesis, tactile/painful hypesthesia and sphincter disturbances of 15 days duration. Cutaneous-pulmonary blastomycosis was diagnosed 17 years ago. Myelotomography showed a blockade of T3-T4 (intramedullary lesion). The lesion surgically removed was a Paracoccidioides brasiliensis granuloma. Treatment with sulfadiazine was started after the surgery. Follow-up of 15 month showed an improvement of the clinical signs. Case 2: a 57-year old male was admitted elsewhere 6 months ago and, with a radiologic diagnosis of pulmonary paracoccidioidomycosis, was treated with amphotericin B. He progressively developed paresthesia and tactile/ pain anaesthesia on the left side, sphincter disturbances and tetraparesis with bilateral extensor plantar response and clonus of the feet. Myelotomography showed a blockade of C4-C6 (intramedullary lesion). The lesion was not found during surgical exploration and the patient deteriorated and died. Post-mortem examination revealed an intramedullary tumor above the site of the mielotomy (Paracoccidioides brasiliensis granuloma). The preoperative diagnosis of intramedullary paracoccidioidomycotic granulomas is difficult because the clinical and radiologic manifestations are uncharacteristic. Clinical suspicion was possible in our cases based on the history of previous systemic disease. Contrary to intracranial localizations, paracoccidioidomycotic granulomas causing progressive spinal cord compression may require early surgery because response to clinical treatment is slow and the reversibility of neurological deficits depends on the promptness of the decompression. São relatados dois casos de granuloma blastomicótico intramedular. A paracoccidioidomicose é micose sistêmica que atinge predominantemente a mucosa bucofaríngea, pulmões, linfonodos e vísceras e infrequentemente o sistema nervoso. A localização medular é rara. Caso 1: paciente masculino, de 55 anos, admitido com parestesias, hipoestesia táctil/dolorosa, paraparesia crural e distúbios esfincterianos. Tinha diagnóstico de blastomicose cutâneo-pulmonar há 17 anos. A mielotomografia mostrou bloqueio em T3-T4 (lesão intramedular). A lesão removida cirurgicamente revelou-se um granuloma blastomiótico. Após a cirurgia foi tratado com sulfadiazina. Durante o seguimento (15 meses) apresentou melhora do quadro clínico. Caso 2: paciente masculino, de 57 anos, internado em outro hospital há 6 meses por blastomicose pulmonar e tratado com anfotericina B. Desenvolveu parestesias, hipoestesia táctil/dolorosa à esquerda, distúrbios esfincterianos e tetraparesia com sinal de Babinski bilateral e clonus nos pés. A mielotomografia mostrou bloqueio de C4-C6 (lesão intramedular). A lesão não foi encontrada durante a cirurgia e o paciente piorou e faleceu. A necrópsia revelou um granuloma blastomicótico intramedular, acima do local da mielotomia. O diagnóstico dos granulomasblastomicóticos intramedulares apresenta dificuldades porque as manisfestações clínicas e radiológicas são incaracterísticas. Nos casos relatados, a suspeita clínica foi baseada nos antecedentes de doença sistêmica prévia. Para os granulomas blastomicóticos raquídeos que causam compressão medular progressiva, ao contrário dos encefálicos, a cirurgia precoce deve ser considerada, pois a regressão com o tratamento clínico é lenta e a reversibilidade dos deficits neurológicos depende da rapidez da descompressão medular.